Postnatal care service utilization and associated factors among women in Goba woreda, Bale zone, Ethiopia: A community based cross-sectional study - Wordofa, Debebe; Hail, Asfaw; Lamore, Yonas; Lette, Abate (Journal of Maternal and Child Health, 2021)
Background: Postnatal care of mothers is essential to reduce maternal morbidity and mortality. Providing postnatal care to recently delivered mothers is quite essential. The aim of the study was to determine the postnatal care utilization and associated factors among women who gave birth in the last 12 months in Goba woreda, Bale Zone, Ethiopia, 2020. Subjects and Method: A community based quantitative cross-sectional study was conducted in Goba woreda from March to April, 2020 among reproductive age group mothers who gave birth the in last 12 months prior this data collection. In this study 422 subjects were conducted using Lottery method to select them. The independent variables were socio-demographics charctestics and obstetrics’ health related factors with outcome variable of postnatal care service utilization. Binary and multivariable logistic regressions analysis were computed to evaluate the factors associated with postnatal care services utilization. Results: In this study a total of 422 women were interviewed with a response rate of 100%. Out of the total respondents, 178 (42.2%) utilized postnatal care service after delivery within six weeks of their last birth. Educational level of mothers (OR= 1.96; 95% CI= 1.06 to 3.62; p= 0.050) maternal knowledge on postpartum danger sign & symptoms (OR= 1.78; 95% CI= 1.16 to 2.72; p= 0.010) pregnancy desire (OR= 1.89; 95% CI= 1.67 to 3.35; p= 0.050) ANC visit (OR= 2.80; 95% CI= 1.32 to 5.97; p= 0.010) and place of deliver (OR= 2.09; 95% CI= 1.30 to 3.34; p= 0.010) had showed statistical significant association with postnatal care utilization. Conclusion: More than half of respondents in Goba woreda were not utilized postnatal care service. Maternal educational status, maternal knowledge on postnatal danger signs and symptom, pregnancy desire for youngest child, ANC attendance and place of delivery found to be independent predictors for PNC service utilization.